2013
DOI: 10.1016/j.mhpa.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy for Life Taekwondo pilot study: A preliminary evaluation of effects on executive function and BMI, feasibility, and acceptability

Abstract: There is growing consensus that exercise improves cognitive functioning, but research is needed to identify exercise interventions that optimize effects on cognition. The objective of this pilot study was to evaluate Taekwondo implemented in public middle school physical education (PE). Two classes were randomly assigned to either: five sessions per week of PE or three sessions of PE and two sessions of Taekwondo. In PE sessions, evidence-based curriculum to address the Presidential Core Fitness Guidelines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
2
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 15 publications
2
74
2
11
Order By: Relevance
“…It is plausible that qualitative exercise interventions that are mentally challenging, lead to procedural and declarative skill development, and stress the formulation of strategies would alter metacognitive processes that build upon basic executive functions. Studies conducted by Lakes et al 34,54 and Pesce et al, 32 and Crova et al 38 that employ qualitative interventions provide preliminary evidence for the instantiation of skills and utilization of strategies. Furthermore, interesting studies in children's sports training show that enrichment interventions may promote the development of tactical creativity skills that involve executive control and the acquisition, usage, and transfer of declarative, procedural, and strategic knowledge Exercise and Children's Cognition within the sport environment.…”
Section: Does Exercise Alter Children's Metacognitive Function?mentioning
confidence: 99%
“…It is plausible that qualitative exercise interventions that are mentally challenging, lead to procedural and declarative skill development, and stress the formulation of strategies would alter metacognitive processes that build upon basic executive functions. Studies conducted by Lakes et al 34,54 and Pesce et al, 32 and Crova et al 38 that employ qualitative interventions provide preliminary evidence for the instantiation of skills and utilization of strategies. Furthermore, interesting studies in children's sports training show that enrichment interventions may promote the development of tactical creativity skills that involve executive control and the acquisition, usage, and transfer of declarative, procedural, and strategic knowledge Exercise and Children's Cognition within the sport environment.…”
Section: Does Exercise Alter Children's Metacognitive Function?mentioning
confidence: 99%
“…Previous studies have found that regular TKD participation can provide physiological (e.g., aerobic capacity, body composition, and flexibility) and psychological health benefits (e.g., life satisfaction, behavioral and social improvements) (Byeon, Kwon, & Park, 2008;Fong & Na, 2011;Kim, Dattilo, & Heo 2011;Lakes, 2013;Lakes et al, 2013). Motives for participating in TKD with youth include skill mastery, the uniqueness of the sport, fun, and physical benefits (Zeng, Cynarski, Baatz, & Park, 2015), while adults have reported self-realization and health benefits as primary motives (Ko, Seok, & Kwon, 2013).…”
Section: Taekwondomentioning
confidence: 99%
“…Dessa forma, observa-se a viabilidade da adição de ingredientes funcionais em barras de cereais. Fato que poderá colaborar para que os praticantes de lutas marciais tenham uma dieta com melhor perfil nutricional, já que as fibras auxiliam na absorção de nutrientes, como vitaminas e minerais, melhoram o trânsito intestinal e reduzem a fadiga pós-treino 2,3 . Na Figura 2 é possível verificar o IA da barra de cereal padrão e daquelas adicionadas de inulina, em relação aos atributos aparência, aroma, sabor, textura, cor e aceitação global.…”
Section: Análise Sensorialunclassified
“…Exemplos como o judô, taekwondo e karatê são mundialmente conhecidos enquanto esporte e, devido a esses fatores, sua procura vem aumentando 1 . A prática deste tipo de exercício exige do organismo uma nutrição equilibrada, a qual é essencial para a manutenção da saúde e composição corporal, bom desempenho físico, melhora de rendimento e redução da fadiga 2,3 . As modificações fisiológicas causadas pelo exercício físico, se não compensadas acabam levando à desgastes que podem gerar alterações na microbiota intestinal do indivíduo, resultando no aumento das bactérias patogênicas.…”
Section: Introductionunclassified